Concentrations of Bioactives and Functional Factors in Destoned Virgin Olive Oil: The Case Study of the Oil from Olivastra di Seggiano Cultivar - Federico Ranalli; Alfonso Ranalli; Stefania Contento; Maria Casanovas; Mariangela Antonucci; Guido Di Simone (Journal of Pharmacy and Nutrition Sciences, 2012)
This work reports on the composition and bionutritional value of destoned (vs. whole) virgin olive oil from Olivastra di Seggiano cultivar, one having wild features, which is cultivated in olive areas of Tuscany Region, Italy. Removal of the stone from fruit before processing is an innovative technique that strongly enhanced the already high quality level of this oil variety. There was for this product marked interaction between genetic background and destoning. An in-depth analytical investigation from 2008 to 2010 showed how the innovated olive extraction process led to an improved product standing out for its peculiar features, related mainly to the improved biophenol and volatile composition, as well as to higher concentrations of the lipophilic and vitamin antioxidants (tocopherols and tocotrienols). It had slowly higher levels of oleocanthal (p-HPEA-EDA), which was found to be a nutraceutical factor. Its head-space aroma even displayed new volatile phytomolecules and also had higher levels of green volatiles from the LOX-pathway (having as precursors the polyunsaturated fatty acids containing a cis-cis-1,4-pentadiene system). Among the other bioactives are to be highlighted the significant levels of trans-β-carotene and xanthophylls (lutein, violaxanthin, neoxanthin and other minor carotenoids), whose amount however was not higher with respect to reference oil. Its enhanced bionutritional value was confirmed by the increased intensity of valuable tasting notes, among which stood out the artichoke flavour. Finally it showed higher resistance to autoxidation and longer shelf-life.